Affirmative action and the university : race, ethnicity, and gender in higher education employment - Rai, Kul B. (University of Nebraska Press, 2000)
Affirmative Action and the University is the only full-length study to examine the impact of affirmative action on all higher education hiring practices. Drawing on data provided by the Equal Employment Opportunity Commission and the U.S. Department of Education's National Center for Education Statistics, the authors summarize, track, and evaluate changes in the gender and ethnic makeup of academic and nonacademic employees at private and public colleges and universities from the late 1970s through the mid-1990s. Separate chapters assess changes in employment opportunities for white women, blacks, Asians, Hispanics, and Native Americans. The authors look at the extent to which a two-tier employment system exists. In such a system minorities and women are more likely to make their greatest gains in non-elite positions rather than in faculty and administrative positions. The authors also examine differences in hiring practices between public and private colleges and universities. Kul B. Rai is a professor of political science at Southern Connecticut State University. His works include "America in the Twenty-First Century: Challenges and Opportunities in Domestic Politics". John W. Critzer is a professor of political science at Southern Connecticut State University